Parametric study of the thermocline filler concept based on exergy. (June 2018) - Odenthal, Christian; Klasing, Freerk; Bauer, Thomas
Highlights: Extensive parametric study of the molten salt thermocline filler concept with 880 parameters varied. Methodology, where each configuration is adjusted for 8 or 12 h charging time, allowing a realistic comparison. Direct comparison of promising configurations with the two tank storage system. Abstract: In this work, an extensive parametric study of the molten salt thermocline storage concept with filler is presented. The parametric study is coupled with an optimization routine, allowing a better comparison, since it finds only those storage configurations, which can directly substitute the two-tank system in a given power plant. Results show that, compared to the two-tank molten salt system, the thermocline technology achieves high exergetic efficiency at only slightly increased storage volume size and a huge decrease in salt inventory.